EXPLORING PARENTS’ HOME-BASED INVOLVEMENT IN THEIR CHILDREN’S ENGLISH LEARNING: TRIGGERS AND BARRIERS - Cicilia Siwi Triutami; Retno Muljani (IKIP Siliwangi, 2021)
In Indonesian context, English has been taught in elementary school level and parents’ involvement is considered as one of the influencing factors which has contribution to the children’s language learning achievement. The rapid, complex and continuous societal changes in this digital era might impact and alter the possibilities of parents’ involvement in their children’s language learning. The current study explored the triggers and the barriers of parents’ home-based involvement in their children’s English language learning and the features of their involvement. The qualitative research by implementing semi-structured, in- depth interview with four parents of elementary students at one of private schools in Yogyakarta city was conducted. The findings show the three main triggers in parents’ home-based involvement namely: (1) parents’ belief of the importance of English, (2) the implementation of school technological learning tools and (3) parents’ expectation of their children academic achievement. While the barriers that parents encounter in their involvement are: (1) parents’ lack of time, (2) parents’ unproficiency in English and (3) parents’ unfamiliarity with the use of technological tools. As the features of involvement, the study reveals parents’ monitoring, accompaniment, assistances in their children’s home-learning activities, providing some additional English learning media and financing English private course. Keywords: Barriers, Children’s English Language Learning, Parents’ Home-Based Involvement, Triggers